Minimally Invasive Transforaminal Lumbar Interbody Fusion: Comparison of Grade I Versus Grade II Isthmic Spondylolisthesis - MASSEL, DUSTIN H. (Int J Spine Surg, 2020)
BACKGROUND: Minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) is often used to treat low-grade isthmic spondylolisthesis (IS). No studies have compared surgical outcomes for grade I and II IS following MIS-TLIF. Therefore, the objective of the current study was to compare outcomes between patients with grade I and II IS following MIS-TLIF. METHODS: A retrospective cohort analysis was performed on a prospectively maintained database of patients who underwent a primary 1-level MIS-TLIF for treatment of IS between 2007 and 2015. Grade I patients underwent a unilateral tubular approach with a single interbody cage and bilateral pedicle screw instrumentation. Grade II patients underwent a bilateral tubular approach with bilateral interbody cage and pedicle screw placement. Baseline patient demographics and characteristics were compared using Student t test and χ(2) analysis. Differences in peri- and postoperative outcomes were assessed using Poisson regression with robust error variance or linear regression adjusted for perioperative variables. RESULTS: A total of 58 patients with IS underwent MIS-TLIF; 21 (36.2%) were grade I and 37 (63.8%) were grade II. The grade I cohort was younger (42.2 versus 50.6 years, P = .029); no other differences in preoperative variables were observed. No significant differences in operative time, estimated blood loss, length of hospital stay, postoperative visual analogue scale scores, or complication and revision rates were demonstrated between cohorts. Arthrodesis rate was lower in the grade I cohort, though not statistically significant. CONCLUSIONS: Despite the grade I cohort being younger with less-severe diagnoses, the grade II cohort experienced similar outcomes. This finding may be due to the grade II cohort receiving bilateral cages, potentially providing a better fusion environment. CLINICAL RELEVANCE: These results suggest that MIS-TLIF provides sufficient stabilization and fusion for treatment of grade II IS despite increased vertebral body displacement. In addition, MIS-TLIF with bilateral approach and interbody cage placement should be examined for treatment of high-grade IS cases.